DYNAMICS OF CONFLICT BETWEEN LOCAL AND ANDON FISHERMEN IN THE JORONG FISHING GROUND (CASE ANALYSIS OF THE USE OF ILLEGAL FISHING GEAR): DINAMIKA KONFLIK NELAYAN LOKAL DAN ANDON DI ZONA PENANGKAPAN IKAN JORONG (ANALISIS KASUS PENGGUNAAN ALAT TANGKAP IKAN ILEGAL) - Muhammad Hassel Yasa Satria; Hamid Abdul Aziz; Muhammad Aulia Rahman; Nadia Oktaviani; Riyanni; Sriwati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
People in South Kalimantan who live in coastal areas generally make their living as fishermen. In fisheries activities, especially fishing, conflict is a social phenomenon that is often found in various water areas. One of the conflicts that occurred was in the Jorong fishing ground area where andon fishermen who came to this area used different equipment than local fishermen. Illegal fishing practices by andon fishermen have become a source of conflict with local fishermen. The aim of this research is to describe the dynamics, influence and efforts to resolve conflicts between local fishermen and andon fishermen in the fishing ground area of Jorong waters. This research uses a qualitative research method, where this method is a type of research that focuses on description and tends to apply analysis with an inductive approach. The research results show that this conflict has been a concern since 2012. The polemic arose because Central Java fishermen used cantrang tools in the coastal waters of South Kalimantan. This conflict between Andon and local fishermen has an impact on local communities both socially and economically. Efforts to resolve the conflict between local fishermen and andon fishermen in Swarangan Village, Jorong District, have been carried out by involving various related agencies which play an important role in mediating and enforcing regulations